If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -8 = 2 + 4x + -8 Reorder the terms: -8 + 3x = 2 + 4x + -8 Reorder the terms: -8 + 3x = 2 + -8 + 4x Combine like terms: 2 + -8 = -6 -8 + 3x = -6 + 4x Solving -8 + 3x = -6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -8 + 3x + -4x = -6 + 4x + -4x Combine like terms: 3x + -4x = -1x -8 + -1x = -6 + 4x + -4x Combine like terms: 4x + -4x = 0 -8 + -1x = -6 + 0 -8 + -1x = -6 Add '8' to each side of the equation. -8 + 8 + -1x = -6 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = -6 + 8 -1x = -6 + 8 Combine like terms: -6 + 8 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2
| 7x-3(c+6)=14 | | 26x+4=18 | | 2x=80-2x | | 0.36/8 | | 10n^2-29n-44=0 | | 445-6x=0 | | -34z=14 | | -((2x)/(x-1)^3)=0 | | 4x^2-49x-900=0 | | 4x-9-6x=2(x+5)-3 | | 0.5x+0.3=.2 | | -5x-12y=15 | | 6*6/2(3)=4 | | -0.5(x-2)=-x-2 | | 2(x-16)=0 | | -((20x)/sqrt(9-20x^2)=2 | | y/8-x/4=1 | | 13x-1=116 | | y=2x^2+(4)x-7 | | -((20x)/(9-20x^2)^(1/2))=2 | | 2x+(3x)=25 | | 4(2-6x)=6(2-4x) | | 18=7p+p^2 | | 1/3v-9/5=-1/2 | | -((20x)/(9-20x^2)^(1/2)) | | (9z)^1/5 | | 1/3-9/5=-1/2 | | 5/9-1/3v=-1/6 | | 3/2x-1/7=-8/5 | | 5*(2/3)=x | | x^2-3xy+y^2+25=0 | | 14=-7/9w |